Relationships of scincid lizards (Mabuya spp.) from the islands of the Gulf of Guinea based on mtDNA sequence data - Jesus, José (2005)
Relationships of Mabuya lizards from the islands of the Gulf of Guinea where estimated using partial 12S rRNA, 16S rRNA and cytochrome b mitochondrial gene sequences. Mabuya maculilabris from São Tomé and Principe are discreet monophyletic units, highly divergent from each other and from mainland populations, indicating M. maculilabris may be a species complex. Mabuya affinis from Principe is similarly distinct from mainland populations of this species. The relationships of Mabuya ozorii from Annobon are unclear, but the three species in the Gulf of Guinea islands are not closely related, indicating multiple independent colonization events. The recent proposal to partition Mabuya into four genera is premature, since at least five distinct genetic lineages can be identified.